Interaksi Sosial Masyarakat Setempat dengan Mahasiswa Asal Pattani Thailand di Kota Bandung - Supian Hahyeejehteh (TEMALI : Jurnal Pembangunan Sosial, 2021)
This study discusses community interaction with students from Pattani, Southern Thailand. As international students living in Bandung, they faced some challenges, especially concerning interaction as social capital for survival. This study used a qualitative method with a case study approach to the Pattani Selatan Thai students who live in the Cipadung Village, Cibiru District, Bandung City. This study found an open interaction between the Cipadung community and students associatively, giving birth to good cooperation in various activities such as celebrating national holidays and Islamic holidays. Pattani Selatan Thailand students carry out social interactions that are openly driven by internal factors from within or psychological and external sociological factors. The interactions that occur are not yet entirely ideal because there are still many limitations and obstacles such as cultural customs, language, ethnic prejudice, and differences in interests. However, students from South Patani Thailand still have an excellent opportunity to interact with the community through the learning process and adaptation of South Patani Thailand students by learning local languages and customs.